2019
DOI: 10.2217/cer-2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

Using flowable gelatin in anterior cervical spine surgery in real-world practice: a retrospective cohort study

Abstract: Aim: To assess the clinical and economic impact of flowable gelatin hemostatic matrix (FGHM) in anterior cervical spine surgery (ACSS). Patients & methods: A total of 451 patients with performed ACSS were included to compare FGHM with conventional hemostatic methods for clinical and cost outcomes using propensity score matching method. Results: The comparisons of the matched 125 pairs observed that FGHM was associated with significantly lower blood transfusion volume (11.2 vs 36.3 ml; p = 0.039), shorter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, vertebral arteries and surrounding veins can be sources of intractable bleeding, and continuous oozing from the vertebral foramens is frequently encountered, making conventional hemostatic techniques the suboptimal solution. The advantages of TGM in cervical spine procedures have previously been advocated, and the usage of these potent hemostatic agent can be justified, regardless of the actual volume of blood loss [ 3 , 22 ]. Several previous studies have indicated that incidental durotomy was associated with increased blood loss [ 23 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, vertebral arteries and surrounding veins can be sources of intractable bleeding, and continuous oozing from the vertebral foramens is frequently encountered, making conventional hemostatic techniques the suboptimal solution. The advantages of TGM in cervical spine procedures have previously been advocated, and the usage of these potent hemostatic agent can be justified, regardless of the actual volume of blood loss [ 3 , 22 ]. Several previous studies have indicated that incidental durotomy was associated with increased blood loss [ 23 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of TGM in cervical spine procedures have previously been advocated, and the usage of these potent hemostatic agent can be justi ed, regardless of the actual volume of blood loss. [12,21] Several previous studies have indicated that incidental durotomy was associated with increased blood loss. [22][23][24][25] This may be due in part to the prolonged operation time needed for dural repair, but other authors have reported that the loss of expansive tension of the dural sac due to cerebrospinal uid leakage leads to the dilatation of the epidural venous plexus, [26] which can result in increased blood loss, necessitating unplanned TGM usage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefor, nding a convenient, fast and effective hemostatic tool is extremely important. Gelatin matrix hemostatic sealant can signi cantly reduce blood loss by promoting coagulation and brin formation [9] . These agents are a mixture of a owable gelatin matrix (bovine or porcine) and a human-derived thrombin component.…”
Section: Introductionmentioning
confidence: 99%